PHYTOCHEMICAL AND ANTIMICROBIAL ACTIVITY TESTS OF TURMERIC TINCTURE AS A DISINFECTANT FOR MEPANDES CEREMONIAL EQUIPMENT IN BALI - Widiari, Ni Nyoman; Tata Arini, Ni Putu Dewi; Karta, I Wayan (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2024)
Background: In the traditional Mepandes ceremony of Bali, one of the key practices involves the use of sangging equipment, including chisels, files, and sharpeners, to smoothen teeth surfaces. Typically, one set of sangging tools is shared among 3-10 individuals, rotating their use. This practice poses a potential risk of disease transmission. The current cleaning methods vary, with some using water and turmeric while others soak the equipment in 5% NaOCl. However, the use of water alone may not ensure proper hygiene, and NaOCl usage presents challenges such as equipment odor and potential health hazards.Aims: The objective of this study is to qualitatively analyze the phytochemical content, inhibitory activity, and total plate count in turmeric tinctures at concentrations of 5%, 10%, and 15% Methods: The tincture is prepared by soaking turmeric simplicia in 70% alcohol for 5 days at concentrations of 5%, 10%, and 15%. In this study, the negative control is 70% alcohol, the positive control is 5% NaOCl, and the treatment includes tinctures at 5%, 10%, and 15%. Phytochemical tests include flavonoid, tannin, saponin, terpenoid, and alkaloid assays. Antimicrobial activity is assessed through total plate count (TPC) and inhibition tests. The results The research results indicate the presence of tannin, flavonoids, and phenols in all three treatments. Based on the antibacterial tests and total plate count, all three tincture solutions can be used as disinfectants. However, for efficiency, a 5% concentration is recommended as it exhibits the same antibacterial strength as the 10% and 15% tinctures.Conclusions:The use of turmeric tincture treatment can be employed as a disinfectant for ceremonial tools since it can inhibit the growth of S. aureus bacteria, and its total plate count value matches that of the positive control.